Perancangan Sistem Pakan Ikan Berbasis Internet of Things Dengan Sistem Pemantuan Menggunakan Bot Telegram Untuk Peternakan Ikan - Nur Bismi; Munawaroh (OKTAL : Jurnal Ilmu Komputer dan Sains, 2023)
The development of information technology is no longer just a complement, but has now become a necessity, one of which is in the world, rapidly developing technology provides various ways to support farmers more efficiently in managing their farms. One of them is a fish feed system based on the Internet of Things. This design aims to overcome the problem of fish cultivators who cannot carry out direct feeding or feeding at the right time due to other activities that must be carried out. The system design uses two methods, namely literature study and observation, literature study is conducted to collect some references related to the research object and learn the basic theory, while observation is carried out to determine the amount of feed needed per day. NodeMCU can be used as a device that receives input and output from a sensor and as a device to connect to the internet because nodeMCU is equipped with an esp8266 chip, by adding a servo as a closing and opening feed, as long as the user can still connect to the internet, it can be done remotely . far. User can monitor using telegram bot with available features.